Rancang Bangun Informasi Toilet Kosong Berbasis Arduino - Nasruddin; Kusmanto, Indar (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2023)
Designing an Arduino-Based Empty Toilet Information Prototype, the electronic components needed are not many, however, the Arduino language, namely C++, a derivative of the C language, is complicated because you have to relearn its functions and how to write them, which is different from Java or Delphi. Implementation of Arduino-based Empty Toilet Information Design is carried out by simulating the process of using paid public toilets and can also be used as a Portable Toilet for other activities such as natural disasters, concerts or other mass activities. How to analyze the design and construction of toilet information, Arduino is needed as a microcontroller which receives input from sensors by writing the C++ program language to give commands to the sensors so that they become input and are executed by Arduino.